(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
Existing modern methods of waste disposal and construction methods, exploitation, phase-out the sludge pit are analyzed in this article. The results of the laboratory experiments of the drilled cuttings components on the soilcement physical and mechanical characteristics are given and the new methods of a sludge pits of water proofing on soilcement watertight screen is presented. Keywords:drilled cuttings, sludge pit, waterproof, soilcement.